Comparison of Learning Outcomes for Acid-Base Materials Using Guided Discovery Models and Guided Inquiry Learning With Buzz Group Discussion Techniques - Sukma, Mutiara; Fitriza, Zonalia (Journal of Educational Sciences, 2022)
The learning process using a scientific approach was not carried out effectively during Covid-19, due to time constraints that affected learning outcomes. Therefore, the learning process was carried out using guided discovery and guided inquiry models with buzz group discussion techniques. This study aims to compare student learning outcomes using guided discovery and guided inquiry models with buzz group discussion techniques for acid-base material. This type of research is an experimental study with a randomized posttest-only comparison group design. Samples were taken by random sampling technique, selected class XI IPA 3 as experimental class 1 (guided inquiry) and XI IPA 4 as experimental class 2 (guided discovery). Learning outcomes were obtained from posttest results and data analysis techniques using a t-test. The results of data processing obtained that the learning outcomes in the experimental class 1 (78.38) were higher than the experimental class 2 (74.82) and the t-test analysis was 0.039. Based on the results of data analysis, it was concluded that learning outcomes using guided inquiry and guided discovery models with buzz group discussion techniques for acid-base class XI IPA MAN 1 Bukittinggi were significantly different.